Makna Interaksi Simbolik Nyiramkeun Benda Pusaka Di Desa Nunuk Baru Kecamatan Maja Kabupaten Majalengka - Teddy Maulana Hidayat Sudirman; Titih Nurhaipah (Universitas Majalengka, 2026)
Nunuk Baru has a close attachment to the Talaga Manggung Kingdom, and that is why the village of Nunuk Baru Lagi was legalized as a village. One of these attachments is that the heirlooms in Nunuk Baru village are inherited from the Talaga Manggung Kingdom and there is an activity that is routinely carried out every year by the Nunuk Baru village government, namely Nyiramkeun Heritage Objects. Some cleavers also have certain symbols representing strength, wisdom, and spirituality. The shape of the machete blade, which is curved at the base and tapered at the end, symbolizes human life which is full of twists and turns and challenges. The prestige on the spear blade, which is formed from a combination of hard and soft metals, symbolizes the diversity of people and a harmonious blend between them. The bronze material itself has a meaning as a symbol of eternity, because bronze is a material that is very durable and does not corrode easily. goong symbolizes the beauty, creativity, and craftsmanship of the maker. Tangguh goong on the keris represents the physical, moral, and spiritual strength possessed by the maker and owner. As for the meaning of each of these processions, the heirlooms in the village of Nunuk Baru have their own uniqueness, starting to maintain ancestral culture that has not been carried out for a long time, increasing the community's economy and community participation to build and introduce the village of Nunuk Baru which has been long considered lost.